Right-wing Authoritarianism, Left-wing Authoritarianism, and pandemic-mitigation authoritarianism() - Manson, Joseph H. (Pers Individ Dif, 2020)
Recent research suggests the validity of the construct of Left-wing Authoritarianism (LWA). Like its well-studied parallel construct Right-wing Authoritarianism, LWA is characterized by dogmatism, punitive attitudes toward dissenters, and desire for strong authority figures. In contrast to RWA, LWA mobilizes these traits on behalf of left-wing values (e.g. anti-racism, anti-sexism, and wealth redistribution). I inductively examined the extent to which RWA and LWA predicted, in April 2020, Americans' endorsement of 19 authoritarian policies and practices intended to mitigate the effects of the COVID-19 pandemic. For 11 of these policies (e.g. abrogating the right to trial by jury for pandemic-related crimes), both RWA and LWA independently positively predicted endorsement. These findings are consistent with recent work showing psychological similarities between the two constructs.